Geographic body size variation in ectotherms: effects of seasonality on an anuran from the southern temperate forest. Issue 1 (December 2015) - Valenzuela-Sánchez, Andrés; Cunningham, Andrew; Soto-Azat, Claudio
Abstract Background Body size variation has played a central role in biogeographical research, however, most studies have aimed to describe trends rather than search for underlying mechanisms. In order to provide a more comprehensive understanding of the causes of intra-specific body size variation in ectotherms, we evaluated eight hypotheses proposed in the literature to account for geographical body size variation using the Darwin's frog (Rhinoderma darwinii ), an anuran species widely distributed in the temperate forests of South America. Each of the evaluated hypotheses predicted a specific relationship between body size and environmental variables. The level of support for each of these hypotheses was assessed using an information-theoretic approach and based on data from 1015 adult frogs obtained from 14 sites across the entire distributional range of the species. Results There was strong evidence favouring a single model comprising temperature seasonality as the predictor variable. Larger body sizes were found in areas of greater seasonality, giving support to the "starvation resistance" hypothesis. Considering the known role of temperature on ectothermic metabolism, however, we formulated a new, non-exclusive hypothesis, termed "hibernation hypothesis": greater seasonality is expected to drive larger body size, since metabolic rate is reduced further and longer during colder, longer winters, leading to decreased energy depletion during hibernation, improved survival and increased longevity (and hence growth). Supporting this, a higher post-hibernation body condition in animals from areas of greater seasonality was found. Conclusions Despite largely recognized effects of temperature on metabolic rate in ectotherms, its importance in determining body size in a gradient of seasonality has been largely overlooked so far. Based on our results, we present and discuss an alternative mechanism, the "hibernation hypothesis", underlying geographical body size variation, which can be helpful to improve our understanding of biogeographical patterns in ectotherms.